School Heads’ Leadership Competence, Teacher Professional Development, and Instructional Quality in Mathematics Classroom Performance - Santuyas, Margie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the predictive influence of school heads’ leadership competence, teacher professional development, and instructional quality on students’ classroom performance in mathematics in public secondary schools in the Division of Bohol for School Year 2025–2026. Anchored on Transformational Leadership Theory, Instructional Leadership Theory, Human Capital Theory, Constructivist Learning Theory, and the Theory of Planned Behavior, the study employed a quantitative, non-experimental correlational design with a predictive approach. Data were collected through structured questionnaires administered to 136 school heads, 295 mathematics teachers, and 381 students selected through stratified sampling. Instruments were based on DepEd standards and the PISA 2022 Analytical Framework, with reliability confirmed through a Cronbach’s alpha of 0.84. Descriptive statistics, Pearson r correlation, and multiple regression analysis were used. Findings revealed that school heads demonstrated high leadership competence, teachers exhibited moderate to high professional development, and instructional quality in mathematics was generally good. Students achieved outstanding classroom performance. Significant relationships were found between leadership competence and teacher professional development, teacher professional development and instructional quality, and leadership competence and instructional quality. However, no significant direct relationships or predictive effects were observed between these variables and students’ classroom performance. The results suggest that leadership and professional development influence student outcomes indirectly through instructional processes. The study recommends strengthening instructional leadership, reflective practice, ICT integration, and higher-order thinking strategies in mathematics instruction. This study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) by promoting improved teaching quality and professional development. It contributes to educational, institutional, and socio-economic sustainability by enhancing human capital, strengthening governance practices, and supporting continuous improvement in mathematics education.